Interferon gamma induces inflammatory responses through the interaction of CEACAM1 and PI3K in airway epithelial cells - Zhu, Yichun (J Transl Med, 2019)
BACKGROUND: Interferon gamma (IFNγ) plays an important role in the development of chronic lung diseases via the production of inflammatory mediators, although the exact mechanism remains unclear. The present study aimed at investigating the potential mechanisms by which IFNγ induced over-production of interleukins through the interaction between carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) and phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K) pathway. METHODS: IFN-γ induced over-production of interleukin (IL) 6 and IL8, and RNA expression of CEACAM1 and its subtypes or PI3K and its subtypes in human bronchial epithelial cells (HBE). The production of IL6 and IL8 or cell proliferation and movement were also evaluated in cell(CEACAM1−) or cell(CEACAM1+) after the induction of IFN-γ. Roles of PI3K subtype proteins, e.g. PI3Kp110α/δ, Akt, p110α/γ/δ/β/mTOR, PI3Kp110α/δ/β, PI3Kp110δ, or pan-PI3K in IFN-γ-induced CEACAM1 subtype alterations were furthermore validated using those proteins of PI3K subtypes. RESULTS: CEACAM1, especially CEACAM1-S isoforms, was significantly up-regulated in HBE cells after treatment with IFN-γ. CEACAM1 played roles in expression of IL-6 and IL-8, and facilitated cellular proliferation and migration. IFN-γ up-regulated the expression of CEACAM1 in airway epithelial cells, especially CEACAM1-S isoforms, promoting cellular proliferation, migration, and the production of inflammatory factors. PI3K (p110δ)/Akt/mTOR pathway was involved in the process of IFN-γ-upregulated CEACAM1, especially CEACAM1-S. On the other hand, CEACAM1 could promote the activation of PI3K/Akt/mTOR pathway. CONCLUSION: IFN-γ could induce inflammatory responses, cellular growth and proliferation through the interaction of CEACAM1 (especially CEACAM1-S isoforms) and PI3K(p110δ)/Akt/mTOR in airway epithelial cells, which might be new alternative of future therapies against epithelial transition from inflammation to cancer. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12967-019-1894-3) contains supplementary material, which is available to authorized users.